Fall prevention implementation strategies in use at 60 United States hospitals: a descriptive study. Issue 12 (18th March 2020) - Turner, Kea; Staggs, Vincent; Potter, Catima; Cramer, Emily; Shorr, Ronald; Mion, Lorraine C
Abstract : Background: To guide fall prevention efforts, United States organisations, such as the Joint Commission and the Agency for Healthcare Research and Quality, have recommended organisational-level implementation strategies: leadership support, interdisciplinary falls committees, electronic health record tools, and staff, family and patient education. It is unclear whether hospitals adhere to such strategies or how these strategies are operationalised. Objective: To identify and describe the prevalence of specific hospital fall prevention implementation strategies. Methods: In 2017, we surveyed 80 US hospitals participating in the National Database of Nursing Quality Indicators who volunteered for the study. We conducted descriptive statistics by calculating percentages for categorical variables and the median and IQR for count variables. Results: A total of 60/80 (75%) of hospitals completed the survey. The majority of hospitals were not-for-profit (98%) and urban (90%); more than half were Magnet (53%), small (53%) and teaching (52%). Hospitals were more likely to use leadership strategies, such as updating fall policies in the past 3 years (98%) but less likely to reward staff (40%). Hospitals commonly used interdisciplinary falls committees (83%) but membership rarely included physicians. Hospitals lacked access to electronic health record tools, such as high-risk medication warnings (27%). Education strategies were commonly used; 100% of hospitals provided fall education at staff orientation, but only 22% educated all employees (not just nursing staff). Conclusions: Our study is the first to our knowledge to examine which expert-recommended implementation strategies are being used and how they are being operationalised in US hospitals. Future studies are needed to document fall prevention implementation strategies in detail and to test which implementation strategies are most effective at reducing falls. Additionally, research is needed to evaluate the quality of implementation (eg, fidelity) of fall prevention interventions.